Improving safety and reliability of Gazelle series vehicles by upgrading frame structures - M. S. Dolmatov; S. A. Ivanov; A. G. Isaev (Безопасность техногенных и природных систем, 2020)
Introduction. The cargo frame is a load-bearing element of the car, since the body and chassis are installed on it. Therefore, high strength requirements are imposed on this node. For safe and reliable operation of the truck, the frame must be adjusted and balanced, since even minor changes in the geometry can negatively affect the overall condition and safe operation of the equipment. This article discusses methods for lengthening the load-bearing elements of trucks on the example of a light-duty car "GAZelle".Problem Statement. Car frame extension is a high-tech process that requires high precision, knowledge, and the use of a wide range of equipment. The extended frame adds a number of advantages to the car, which in turn makes it possible to transport cargo with larger dimensions. The main goal of this work is to enable the car to transport bulky cargo. Also, in the process of extending the frame, it is checked for cracks, breaks and corrosion foci and, if necessary, repairs are made, which increases the reliability, safety and service life of the entire structure as a whole.Theoretical Part. When extending the standard support, all attachments are removed from the car: fuel tanks, body, transmission, drive shaft. All that remains is the cab, the bridge, and the engine. Then the frame is cut in three places.Two cuts are made at a distance of 80 cm in the direction from the cab to the rear bridge, and the last one is made at a distance of 40 cm from the rear bridge in the direction of the rear overhang. Then a longer channel is installed on the frame. It is secured with rivets, bolts, or lap welding. After that, the structure is assembled back. This takes into account the redistribution of loads and the need for high-quality performance of all types of work.Conclusion. The frame is an integral part of not only trucks, but also an important component of passenger cars, as well as light-duty vehicles. Its technical condition is just as important as the condition of, for example, the braking system, as it also ensures the safety of both the driver and pedestrians. The lengthening of the frame in the conditions of repair and mechanical enterprises allows you to increase the load capacity of serial cars of the GAZelle series while ensuring their reliability and safety.